Tradisi, Budaya Dan Potret Keberdayaan Masyarakat Pesisir Sebuah Kajian Etnografi di Pulau Sabang - Onal Syafrizal (Jurnal Community, 2021)
This article attempts to explain to readers how to describe the traditions, culture and empowerment of coastal communities on the island of Sabang. As is well known, Sabang is the main mouthpiece of Aceh's tourist destinations which are often introduced to all countries around the world. Sabang Island is no less attractive than the island of the gods Bali, but somehow Sabang is not as popular as Bali. In fact, Indonesia's initial barometer starts from Sabang, marked by the Zero Kilometer Monument of Indonesia which is located at the end of the island of Sabang. If you claim to be an explorer throughout Indonesia, then it is not worth mentioning that you have traveled throughout Indonesia if you have not set foot in Sabang, especially if you have not arrived at the Zero Kilometer Monument. A portrait of the welfare of the Sabang coastal community is also described in this article. People on Sabang Island have various traditions and cultures that are not necessarily shared by other coastal communities, such as the short market tradition and the culture of napping, subjects who have the authority to trade in the Sabang market have a tradition of opening shops or starting buying and selling activities starting from after dawn (dark morning) until noon (12:00) continue after Asr (16:00) until evening (22:00), meaning from 12:00 to 16:00 all trading activities in the market Sabang is not active. The final conclusion in this article explains that it is time and should the coastal communities be empowered both from the economic, educational, social and cultural sides. When there is a prosperous society, the leader in the area is also categorized as a leader who has the potential to prosper the people. All people in Indonesia certainly want the “welfare” cake, but to make it happen it is very much influenced at the local level, this is what is often forgotten by each individual in general, without realizing small things can actually have a big impact on the social welfare of our society. nowadays. The achievement of the basic needs of the people is a portrait of prosperity and prosperity, because no matter how high the positions of government officials are, they are still serving the people, in fact the people are the real bosses.